KAJIAN PULPING SODA BEBAHAN BAKU PELEPAH PISANG (Musa paradisiaca) (A Study on Pulping Chemical Methods Based of Banana Leaves (Musa paradisiaca): Miati1), Renhart Jemi 2) , Endra Cipta 3) - JHT, Admin (Jurusan Kehutanan, Fakultas Pertanian Universitas Palangka Raya, 2015)
ABSTRACTStem of the banana bunch could to be used as basic material to the making of pulp in order to substitute the basic material of wood. This research was aimed to know the cooker solution concentration of NaOH to produce the best pulp rendement. The research using soda process with NaOH as the cooker solution in the three variation of concentration, i.e. 5%, 10%, and 15%. Research result showed that NaOH with concentration of 5% produce the best pulp rendement, namely 85.58%, they were comprised 39.98% of pulp rendement filtrate and 44.6% of uncooked rendement. Keywords: Concentration of NaOH, pulping soda, stem of banana